2014
DOI: 10.1038/ejhg.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

A decade of molecular genetic testing for MODY: a retrospective study of utilization in The Netherlands

Abstract: Genetic testing for maturity-onset diabetes of the young (MODY) may be relevant for treatment and prognosis in patients with usually early-onset, non-ketotic, insulin-sensitive diabetes and for monitoring strategies in non-diabetic mutation carriers. This study describes the first 10 years of genetic testing for MODY in The Netherlands in terms of volume and test positive rate, medical setting, purpose of the test and age of patients tested. Some analyses focus on the most prevalent subtype, HNF1A MODY. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…As genetic testing for MODY increased over the span of the study, more cases were discovered and the average age of referral for testing increased in HNF1A -MODY cases (25.7 during 2003–2004 to 29.2 during 2009–2010, p=0.022). (26) These examples of centralized monogenic diabetes testing facilities allow relatively comprehensive population studies regarding the patient characteristics, physician criteria, and testing outcome dynamics of MODY diagnosis.…”
Section: Mody Epidemiology Studiesmentioning
confidence: 99%
“…As genetic testing for MODY increased over the span of the study, more cases were discovered and the average age of referral for testing increased in HNF1A -MODY cases (25.7 during 2003–2004 to 29.2 during 2009–2010, p=0.022). (26) These examples of centralized monogenic diabetes testing facilities allow relatively comprehensive population studies regarding the patient characteristics, physician criteria, and testing outcome dynamics of MODY diagnosis.…”
Section: Mody Epidemiology Studiesmentioning
confidence: 99%
“…In The Netherlands, for example, it was estimated that there should be ∼20,000 MODY patients [6]; however, until 2012, only 502 HNF1A, GCK and HNF4A patients were genetically diagnosed [7], and it is unknown how many patients were clinically diagnosed. A large number of patients have not been tested, even though genetic identification of MODY may have several benefits.…”
Section: Introductionmentioning
confidence: 99%
“…From a retrospective study in the UK population (between 1996 and 2009), the prevalence of MODY was reported to be approximately 100 cases per 10 6 population, with a large variability among UK provinces . Other estimates from population‐based childhood diabetes registries range between 2.5–5 cases per 100 000 in several European countries and 2.1 cases per 100 000 in American children from the SEARCH for Diabetes in Youth Study . A high frequency (>20 %) of clinically suspected MODY was reported among patients with T2D younger than 25 years of age in south India, but no genetic characterization was performed.…”
Section: Genetic Subtypes and Clinical Spectrum Of Monogenic Diabetesmentioning
confidence: 99%